Analysis of occupational health and safety management systems implementation in serving COVID-19 patients at the Tanjungpura University Hospital, Pontianak - Pratiwi, Roesmiyanti; Surono, Agus; Qaimamunazalla, Hayu (Universitas Gadjah Mada, 2022)
Purpose: This study analyzes the implementation of the Occupational Health and Safety Management System in serving COVID-19 patients at the Tanjungpura University Hospital, Pontianak. Methods: This type of research is a qualitative descriptive study using a case study approach. The research location is Tanjungpura University Hospital, Pontianak. There were 10 informants in the study. Data was collected using in-depth interviews and field observations. Results: Implementation of the occupational safety and health management system program in protecting health workers who serve COVID-19 patients at the Tanjungpura University Hospital such as disinfecting, making cubical rooms, preparing special doffing and donning rooms, distributing PPE according to standards, providing vitamins and drinks or nutritious food and conducting special PCR examinations on health workers has been carried out well. Conclusion: Implementing occupational health and safety management at the Tanjungpura University Hospital's plan to protect health workers when serving COVID-19 patients refers to the K3RS guidelines. However, this has not been fully realized, and other fields mostly carry out the implementation.